Entrepreneurship education and entrepreneurship intention among business administration students, Ambrose Alli university, Ekpoma, Edo State, south-south of Nigeria - Ugbomhe, Ugbomhe O.; Akhator, P. A. (Journal of Economic Research & Business Administration, 2023)
This study examined how entrepreneurship education affected students of business administration at Ambrose Alli University, Ekpoma, Nigeria's South-South geopolitical zone to become entrepreneurs. Survey research design was adopted in the study. All undergraduate students at the 400 and 200 level made up the population, which had a sample size of 200. The study used questionnaire for data collection. Data was analyze by the use of statistic tool using Statistical Package for Social Sciences (SPSS) version 20, and presented through mean, standard deviation, percentage and frequencies. Hypotheses were tested using correlation and regression analysis. The study revealed from the findings that entrepreneurship curriculum content and entrepreneurship teaching method influence locus of control and attitude of students to become entrepreneurship respectively. In order to transmit the skills and information necessary to foster in students a good attitude toward becoming entrepreneurs, it was suggested, among other things, that teaching of entrepreneurship studies should have a broad range of teaching technique. Keywords: Entrepreneurship education, intention, curriculum content, locus of control, attitude and teaching methods